Morality in Oscar Wilde‘s The Picture of Dorian Gray - Lamrabat Benkacem-Ziani, Nour Houda (Journal of Artistic Creation and Literary Research, 2025)
The Picture of Dorian Gray is the only novel written by Oscar Wilde that made a strong impression as much in the Victorian times as the contemporary age. This essay aims at analysing the morality behind the story of Dorian Gray through a close philosophical approach; mainly, through Nietzsche‘s criticism on morality. Furthermore, the objectives of this paper are: to understand the social background in which works such as Wilde‘s The Picture of Dorian Gray and Nietzsche‘s On the Genealogy of Morality existed, to come to some conclusions about the intention of Wilde when he defended the purpose of aestheticism considering that many of his works dealt with morality and to reflect on the role of morality in art.